PERSEPSI MAHASISWA ARSITEKTUR UPN VETERAN JAWA TIMUR PADA TERMINOLOGI RUANG DAN DESAIN ARSITEKTURAL - Ajeng Ajeng; Endang Sholihatin; Nindira Novilia (LPPM Universitas Cipta Mandiri, 2024)
This research was conducted with several objectives to be achieved in this research, among others: (1) to find out the use of language and terminology that can affect individual perceptions in understanding, interpreting, and feeling a space in architectural design; (2) to find out the influence of language on the creation of space design so as to form an understanding of aesthetic preferences and feelings that arise towards architectural design elements; (3) to find out the use of language between architects, clients, and end users that affect design results and user understanding of a space, (4) the impact of differences in language use by end users in producing perceptions and interpretations of a space and architectural design. This research method uses mixed methods, namely field observation with qualitative methods and data collection through respondent questionnaires with quantitative methods. The conclusions in this study: (1) It can be more effective in communicating an understanding of an architectural design in general, for example